2014
DOI: 10.4161/21645515.2014.969613
|View full text |Cite
|
Sign up to set email alerts
|

Does intention to recommend HPV vaccines impact HPV vaccination rates?

Abstract: Despite recommendations for routine vaccination, HPV vaccination rates among adolescent females have remained low. The objective of this prospective cohort study was to determine whether clinician intention to recommend HPV vaccines predicts HPV vaccine series initiation among previously unvaccinated 11 to 18 year-old girls (N=18,083) who were seen by a pediatric clinician (N=105) from a large primary care network within 3 years of vaccine introduction. We used multivariable logistic regression with generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
(66 reference statements)
0
5
0
1
Order By: Relevance
“…In this survey, 26% of physicians reported concerns about the safety of HPVV, significantly higher than concerns reported about the other NIP adolescent vaccines. Although these may not be the only factors contributing to low HPVV rates in Japan, physician recommendation is recognized as one of the most powerful predictors of HPVV acceptance [21]. Several studies have reported that provider-focused interventions, including provision of information about adolescent vaccines, have the potential to improve immunization coverage [7,8,[32], [33], [34], [35], [36]].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this survey, 26% of physicians reported concerns about the safety of HPVV, significantly higher than concerns reported about the other NIP adolescent vaccines. Although these may not be the only factors contributing to low HPVV rates in Japan, physician recommendation is recognized as one of the most powerful predictors of HPVV acceptance [21]. Several studies have reported that provider-focused interventions, including provision of information about adolescent vaccines, have the potential to improve immunization coverage [7,8,[32], [33], [34], [35], [36]].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the United States (US), a country with a strong immunization program and recommendations, several studies report barriers that make increasing adolescent immunization coverage difficult including safety concerns, lack of knowledge about HPVV, no provider recommendation, personal beliefs, lack of access to healthcare services and competing priorities in an adolescent's schedule (e.g., extra-curricular activities, low priority for seeking medical care) [[9], [10], [11], [12], [13]]. Provider-related barriers have also been reported in the US, such as lack of knowledge about HPVV, negative attitudes toward adolescent immunizations, inconsistent strength of recommendation, and missed opportunities [[14], [15], [16], [17], [18], [19], [20], [21]].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies that examined intention among clinicians, rates varied widely, from 16% to 96%. 17,[19][20][21][22][23]33,37,41,44,57,69,71 The mean for intention rates was 66.9 (SD ¼ 23) and the median was 73; the 16% intention rate was an outlier. In 2 studies that examined intention according to patient age, intention was higher for 13-to 18-year-olds (92%-96%) than 11-to 12-yearolds (73%-78%).…”
Section: Clinicians' Attitudes and Beliefs About Recommending Hpv Vaccinesmentioning
confidence: 99%
“…Die Differenz zwischen der positiven Einstellung gefragter Ärztinnen und Ärzte und den erreichten Impfquoten zeigte sich auch in Befragungen in den USA [32]. Weitere internationale Studien schlussfolgern, dass insbesondere bei der HPV-Impfung zusätzliche Faktoren berücksichtigt werden müssen, die den Zusammenhang zwischen der Impfempfehlung durch den Arzt und der finalen Impfentscheidung beeinflussen: Insbesondere die von den Eltern wahrgenommenen Sicherheitsbedenken der Impfung und die Annahme, die Impfung sei nicht notwendig, spielen eine wichtige Rolle [33,34].…”
Section: Impfempfehlung Und Impfangebot Gegen Hpvunclassified